Surface diffusion : metals, metal atoms, and clusters - Antczak, Grazyna, 1973-; Ehrlich, Gertrude (New York : Cambridge University Press, 2010)
'For the first time, this book unites the theory, experimental techniques and computational tools used to describe the diffusion of atoms, molecules and nanoparticles across metal surfaces. Starting with an outline of the formalism that describes diffusion on surfaces, the authors guide the reader through the principles of atomic movement, before moving on to diffusion under special circumstances, such as the presence of defects or foreign species. With an initial focus on the behaviour of single entities on a surface, later chapters address the movement of clusters of atoms and the interactions between adatoms. While there is a special emphasis on experimental work, attention is paid to the increasingly valuable contributions theoretical work has made in this field. This book has wide interdisciplinary appeal and is ideal for researchers in solid state physics, chemistry as well as materials science, and engineering'--Provided by publisher.
'For the first time, this book unites the theory, experimental techniques and computational tools used to describe the diffusion of atoms, molecules and nanoparticles across metal surfaces. Starting with an outline of the formalism that describes diffusion on surfaces, the authors guide the reader through the principles of atomic movement, before moving on to describe diffusion under special circumstances, such as the presence of defects or foreign species. With an initial focus on the behaviour of single entities on a surface, later chapters address the movement of clusters of atoms and the interactions between adatoms. While there is a special emphasis on experimental work, attention is paid to the increasingly valuable contributions theoretical work has made in this field'--Provided by publisher.
Atomic diffusion on surfaces -- Determination of adatom movements -- Atomic events in surface diffusion -- Diffusion on one-dimensional surfaces -- Diffusion on two-dimensional surfaces -- Diffusion in special environments -- Mechanism of cluster diffusion -- Diffusivities of small clusters -- Diffusion of large clusters -- Atomic pair interactions.
Includes bibliographical references and index.
Keywords: Diffusion; Metals -- Surfaces; Surfaces (Physics)